Veno-Arterial Extracorporeal Membrane Oxygenation in the Treatment of Hemodynamically Unstable Lupus Myocarditis: A Retrospective Case Series Study - Shi YJ; Wang LF; Ma J; Chen Y; Wang WJ; Xie CY (Journal of Inflammation Research, 2022)
Yu-Jun Shi,1,* Li-Feng Wang,1,* Jun Ma,1 Yi Chen,1 Wei-Jun Wang,2 Cui-Ying Xie1 1Department of Emergency, Renji Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 2Department of Cardiovascular Surgery, Renji Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Cui-Ying Xie, Department of Emergency, Renji Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China, Tel +86 13817204797, Email xiecuiying25@126.comObjective: The clinical manifestations and treatment of three patients with hemodynamically unstable lupus myocarditis (LM) were analyzed.Methods: The clinical data of three patients with LM with hemodynamic instability, who were admitted to the emergency ICU of the south hospital of the Renji Hospital, School of Medicine, Shanghai Jiao Tong University of Medicine from January 2018 to December 2021, were collected and analyzed, and relevant literatures were reviewed.Results: Two of the three patients had the first onset of systemic lupus erythematosus. The other patient had mixed connective tissue disease in the past, and lupus was the main manifestation of this disease. At the onset of the disease, all patients had chest tightness and shortness of breath; two patients had a fever, and the markers of myocardial injury increased. Cardiac color Doppler ultrasound indicated that left ventricular ejection fraction decreased significantly. Cardiac insufficiency with cardiogenic shock rapidly appeared as the main manifestation. Two patients immediately started veno-arterial extracorporeal membrane oxygenation (VA-ECMO), and ECMO was also started in one patient after a pacemaker placement was ineffective. For all three patients, high-dose hormones were given to control the primary disease, and then the ECMO machines were removed successfully.Conclusion: VA-ECMO treatment should be implemented in patients with hemodynamically unstable LM as soon as possible to maintain the patient’s hemodynamics and help them overcome the crisis of cardiac dysfunction, allowing more time for primary disease treatment.Keywords: VA-ECMO, lupus myocarditis, hemodynamic instability